The Role of Knowledge Sharing and Innovation in Improving Public Sector Performance: A Literature Review - Muhammad Hafiz; Aldri Frinaldi (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
A government depends on the merits of the bureaucracy that acts as the organizer of the government. Meanwhile, the bureaucracy is very dependent on its human resources. Meanwhile, based on the Apparatus Quality Index, the majority of ASN in Indonesia is in the low and very low categories. So there is a need for performance transformation for ASN. This study aims to analyze the challenges faced in improving performance in the public sector and the role of knowledge sharing and innovation in improving performance in the public sector. This paper uses the library study method which collects data and information by examining relevant books, references, literature, and research journals. The result is that there are three main factors, namely the lack of competence, commitment and cohesiveness that exists in the midst of the current state civil apparatus. Knowledge sharing and innovation have an important role to overcome these weaknesses, namely by forming a community as a forum for sharing knowledge between ASN it can be a means of increasing competence, commitment and building cohesiveness in the midst of ASN